Swimming Instructor Confessions : Age And Gender Are Most Fastest In Capturing Swimming Learning - Rusdi; Lauh, Whalsen Duli Agus (Arus Jurnal Sosial dan Humaniora, 2024)
This Research Aims To Find Out What Age And Gender Children Pick Up Swimming Lessons More Quickly According To The Experience Of Swimming Instructors. The Method Used In This Research Is By Asking Questions Via Google Form Which Are Tailored To The Problem The Researcher Wants To Explore. Questions Are Asked Of The Swimming Instructors And Gain Information And Experience Of The Instructors. The Research Samples Taken In This Study Were 22 Swimming Instructors Who Had Taught Swimming For More Than 5 Years. The Results Show That Based On Recognition From Instructors, Ages 11-13 Years Are 40%, Followed By Ages 8-10 Years At 38%, Ages 5-7 Years 13%, Ages Under 4 Years 6% And Ages 14-16 Years 5%. Meanwhile, Girls Aged 11-13 Years Were 59%, Followed By 8-10 Year Olds With 23%, 13% Aged 5-7 Years, 6% Aged Under 4 Years And 4% Aged 14-16 Years. Meanwhile, In The Gender That Is Faster At Learning To Swim, Men Are 5% More Mature, There Is No Effect At 18%, Women Are 36% Faster, And Men Are 41% Faster.